Ảnh hưởng của hàm lượng magiê đến cấu trúc và hoạt tính của chất xúc tác quang TiO2 trong phản ứng phân huỷ phenol với ánh sáng UV-VIS - Tân và cộng sự, Phạm Phát (Vietnam Journal of Chemistry, 2014)
In this study, MgO loaded TiO2 Degussa P25 powders were prepared by wet impregnation with difference of Mg amount content (i.e 0.5-10%). X-ray patterns studies have not proven the new phases in the MgO loaded TiO2 catalysts as well as BET and SEM studies have not shown the change of its particle size and specific surface area in compared with initial TiO2. The PZC values of TiO2-Mg samples were higher than that of TiO2-P25 and increased with the enhancement of Mg amount. The higher the PZC values were, the lower the saturated adsorption of TiO2 surface to phenol was, because of the basicity of MgO and the negatively charged catalyst surface. The photocatalytic degradation of phenol by using MgO loaded (0.5-10% w/w in Mg) TiO2 catalysts has been studied. Catalyst with 1% w/w Mg content shows a better catalytic behavior than non-loaded TiO2. If the Mg amount was increased more than 1%, the activity of Mg coated TiO2 decreased. The MgO enhancement of photocatalytic activity of TiO2 with optimal content 1% Mg under UV-Visible light may be due to the ability of trapping of photogenerated electron of MgO.